2022
DOI: 10.3390/diagnostics12040894
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of Unknown Primary (CUP) versus CUP Turned to Primary Carcinoma of the Head and Neck—An Analysis of Diagnostic Methods and the Impact of Primary Tumor on Clinical Outcome

Abstract: Background. The purpose of this study was to analyze the value of different diagnostic methods in detecting the primary site and the impact of primary tumors on the clinical outcome of carcinoma of unknown primary (CUP). Methods. In this multicenter, retrospective study, 124 patients with true CUP (n = 94) and CUP turned to primary carcinoma (n = 30) were included. Patients with evidence of primary site during the clinical examination were excluded a priori. The diagnostic procedure was comprised of imaging an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Subsequently, a primary tumor site could be identified in 13 out of these 113 patients (11%). The detection rate of a primary tumor site in patients originally being classified as having a CUP is known to vary between 10 and 40% according to the literature and could be increased more recently by means of newly available diagnostic tools, including NGS or molecular profiling [31][32][33][34][35]. Since targeted therapy approaches are available, an accurate characterization of the tumor is essential for the detection of potentially targetable molecular alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a primary tumor site could be identified in 13 out of these 113 patients (11%). The detection rate of a primary tumor site in patients originally being classified as having a CUP is known to vary between 10 and 40% according to the literature and could be increased more recently by means of newly available diagnostic tools, including NGS or molecular profiling [31][32][33][34][35]. Since targeted therapy approaches are available, an accurate characterization of the tumor is essential for the detection of potentially targetable molecular alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Faisal et al reported the results of a multicenter, retrospective study, analyzing the value of different diagnostic methods in detecting the primary tumor site in 124 patients of carcinoma of unknown primary, and the impact of primary tumors on their clinical outcome. 4 The diagnostic procedure comprised of nasopharyngoscopy, imaging, tonsillectomy, and panendoscopy. Despite extensive diagnostic work-up, the primary site remained unknown in 75.8%.…”
Section: Identification Of Primary Tumor Sitementioning
confidence: 99%
“…Furthermore, the PET/CT was not superior to the conventional imaging in the detection of the primary tumor site. 4 …”
Section: Identification Of Primary Tumor Sitementioning
confidence: 99%
See 1 more Smart Citation
“…The HNCUP diagnosis is made by exclusion, as it is represented in Figure 1 . The initial diagnostic workup consists of a thorough collection of anamnestic data, such as personal and familiar history of malignancies and the presence of risk factors (e.g., immunosuppressive factors), the clinical symptoms at the onset, diagnostic imaging, and complete H&N physical examination [ 4 , 5 , 6 ]. The age of onset of H&N cancer peaks at 60–70 years, and males are more affected than females.…”
Section: Introductionmentioning
confidence: 99%